Students’ Engagement and Interest in Learning Writing through Mind Mapping Technique - Wahyu Wahyu (Institut Agama Islam Negeri Palopo, 2019)
The objective of this research was to find out whether the use of mind mapping technique is effective or ineffective in improving students’ engagement and interest in learning writing. The researcher employed quantitative method with the quasi-experimental design. The research was conducted to the fourth-semester students of English Study Program of IAIN Bone. The data were collected by using observation checklist, writing test, and questionnaire. The data from observation checklist were used to find out students’ behavioral engagement, in this case, students’ participation in experimental group which was taught writing subject through mind mapping technique. The writing test was given twice for both experimental and control group to investigate the students’ writing ability which shows students’ cognitive engagement before and after the treatment was conducted. It can be concluded that the use of mind mapping technique in learning writing is effective to increase students’ engagement and interest. Moreover, further analysis shows that students’ behavioral engagement is higher than students’ cognitive engagement and students’ expressed interest increases higher than other types of interest due to the technique used which was mind mapping technique.